2001
DOI: 10.1007/s002560000296
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of the knee in marathon runners before and after competition

Abstract: In healthy individuals no negative long-term-effects were experienced. Pre-existing high-grade lesions of the menisci might be a predisposing risk for osteoarthritis, triggered by the stress of long-distance running.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 4 publications
6
84
0
2
Order By: Relevance
“…There are only a few studies about acute lesions of the knee that occur after running a marathon and that are visible with MRI immediately after the running. To our knowledge, only two studies investigated changes in the menisci and ligaments of the knee and included only six and eight participants, respectively [2,6]. Thus, the question of whether or not or to what extent running a single marathon causes acute lesions of the knee has not been fully answered.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few studies about acute lesions of the knee that occur after running a marathon and that are visible with MRI immediately after the running. To our knowledge, only two studies investigated changes in the menisci and ligaments of the knee and included only six and eight participants, respectively [2,6]. Thus, the question of whether or not or to what extent running a single marathon causes acute lesions of the knee has not been fully answered.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond this degree of flexion, the limiting factor becomes the diameter of the scanner bore. In other studies where the aim was to image the knee in flexed position, only general-purpose surface coils have been used [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Question 19 (internal validity on bias) was also scored poorly. All studies well addressed on questions 1-7 (reporting), 13 (external validity), [16][17][18]20 (internal validity on bias) and 26 (internal validity on confounding).…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
“…Numerous studies have employed MRI to examine pathological, morphological and/or biochemical changes in response to long-distance running, but such studies have mainly focused on the knee joint [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Many of these studies found significant changes including bone marrow edema (BME), joint effusion and cartilage thickness and volume, but such changes seem to return to baseline after a rest period (1 h to 8 weeks) [13,20,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation